Extracellular Vesicles: An Emerging Regenerative Treatment for Oral Disease - He, Fanzhen; Li, Lu; Fan, Ruyi; Wang, Xiaoqian; Chen, Xu; Xu, Yan (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles (EVs) are small lipid-enclosed particles containing biological molecules such as RNA and proteins that have emerged as vital modulators of intercellular communication. Increasingly, studies have shown that EVs play an essential role in the occurrence and prognosis of oral diseases. EVs are increasingly considered a research hotspot of oral diseases. In addition, the characteristics of carrying active molecules have also been studied in oral tissue regeneration. Evidence has shown that EVs regulate the homeostasis of the inflammatory microenvironment, promote angiogenesis, and repair damaged tissues. In this review, we summarized the characteristics of EVs and highlighted the role of EVs in oral tissue regeneration, including dental pulp, periodontal tissue, cartilage, and bone. We also discussed their deficiencies and prospects as a potential therapeutic role in the regeneration treatment of oral disease.